Quick Guide to Psychiatric Emergencies Tools for Behavioral and Toxicological Situations (Springer International Publishing, 2018)
This volume provides an "on-the-go" guide to the most common behavioral emergencies a physician may encounter. Each chapter represents a disease state or symptom cluster and concisely summarizes the disease state, provides background, symptoms and signs, differential diagnoses, and immediate and long-term treatment options. All chapters conclude with a diagnosis or treatment algorithm or another easy-to-use visual tool. Chapters named after a specific disease state or symptom cluster, arranged alphabetically for use in the field. The text begins with chapters covering patient evaluation: getting a good history, suicide risk assessment, physical exam, and when and how to use studies. Written by experts in psychiatry and emergency medicine, this text is the first to consider both medical perspectives in a concise guide. Quick Guide to Psychiatric Emergencies is an excellent resource for psychiatrists, emergency medicine physicians, residents, nurses, and other medical professionals that handle behavioral emergencies on a regular basis.